Accessing the bottleneck in all-solid state batteries, lithium-ion transport over the solid-electrolyte-electrode interface. Issue 1 (December 2017) - Yu, Chuang; Ganapathy, Swapna; Eck, Ernst; Wang, Heng; Basak, Shibabrata; Li, Zhaolong; Wagemaker, Marnix
Abstract Solid-state batteries potentially offer increased lithium-ion battery energy density and safety as required for large-scale production of electrical vehicles. One of the key challenges toward high-performance solid-state batteries is the large impedance posed by the electrode–electrolyte interface. However, direct assessment of the lithium-ion transport across realistic electrode–electrolyte interfaces is tedious. Here we report two-dimensional lithium-ion exchange NMR accessing the spontaneous lithium-ion transport, providing insight on the influence of electrode preparation and battery cycling on the lithium-ion transport over the interface between an argyrodite solid-electrolyte and a sulfide electrode. Interfacial conductivity is shown to depend strongly on the preparation method and demonstrated to drop dramatically after a few electrochemical (dis)charge cycles due to both losses in interfacial contact and increased diffusional barriers. The reported exchange NMR facilitates non-invasive and selective measurement of lithium-ion interfacial transport, providing insight that can guide the electrolyte–electrode interface design for future all-solid-state batteries. The large impedance at the interface between electrode and electrolyte poses a challenge to the development of solid-state batteries. Here the authors utilize two-dimensional lithium-ion exchange-NMR to monitor the spontaneous lithium-ion transport, providing insight into the interface design.